Effects of ammonium-based nitrogen addition on soil nitrification and nitrogen gas emissions depend on fertilizer-induced changes in pH in a tea plantation soil - Wang, Jing; Tu, Xiaoshun; Zhang, Huimin; Cui, Jingya; Ni, Kang; Chen, Jinlin; Cheng, Yi; Zhang, Jinbo; Chang, Scott X. (The Science of the total environment, 2020)
Tea (Camellia sinensis L.) plants have an optimal pH range of 4.5–6.0, and prefer ammonium (NH4+) over nitrate (NO3−); strong soil acidification and nitrification are thus detrimental to their growth. Application of NH4+-based fertilizers can enhance nitrification and produce H+ that can inhibit nitrification. However, how soil acidification and nitrification are interactively affected by different NH4+-based fertilizers in tea plantations remains unclear. The objective of this research was to evaluate the effect of the application of different forms and rates of NH4+-based fertilizers on pH, net nitrification rates, and N2O and NO emissions in an acidic tea plantation soil. We conducted a 35-day aerobic incubation experiment using ammonium sulphate, urea and ammonium bicarbonate applied at 0, 100 or 200 mg N kg−1 soil. Urea and ammonium bicarbonate significantly increased both soil pH and net nitrification rates, while ammonium sulphate did not affect soil pH but reduced net nitrification rates mainly due to the acidic nature of the fertilizer. We found that the effect of different NH4+-based nitrogen on soil nitrification depended on the impact of the fertilizers on soil pH, and nitrification played an important role in NO emissions, but not in N2O emissions. Overall, urea and ammonium bicarbonate application decoupled crop N preference and the form of N available in spite of increasing soil pH. We thus recommend the co-application of urease and nitrification inhibitors when urea is used as a fertilizer and nitrification inhibitors when ammonium bicarbonate is used as a fertilizer in tea plantations. [Display omitted] •How NH4+-N input affects soil pH and nitrification in tea plantations is unclear.•We determined pH, net nitrification rate, and NOx fluxes under NH4+-N input.•NH4+-based N addition affected net nitrification rates by changing soil pH.•Nitrification inhibitor should be co-applied with urea and NH4HCO3.